Silicon carrier depletion modulator with 10 Gbit/s driver realized in high‐performance photonic BiCMOS. Issue 1 (25th November 2013) - Thomson, David J.; Porte, Henri; Goll, Bernhard; Knoll, Dieter; Lischke, Stefan; Gardes, Frederic Y.; Hu, Youfang; Reed, Graham T.; Zimmermann, Horst; Zimmermann, Lars
<x xml:space="preserve">Abstract</x> Optical modulators based upon carrier depletion have proven to be effective at achieving high speed operation in silicon. However, when incorporated into Mach‐Zehnder Interferometer structures they require electronic driver amplifiers to provide peak to peak drive voltages of a few volts in order to achieve a large extinction ratio. For minimal performance degradation caused by the electrical connection between the driver and the modulator monolithic integration in the front end of the process is the preferred integration route. The formation of electronic driver amplifiers in BiCMOS is advantageous over CMOS in terms of achievable performance versus cost. In this work the first monolithic photonic integration in the electronic front‐end of a high‐performance BiCMOS technology process is demonstrated. Modulation at 10 Gbit/s is demonstrated with an extinction ratio >8 dB. The potential scalability of both the silicon photonic and BiCMOS elements make this technology an attractive prospect for the future. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>